Arrested Development? The Promises and Paradoxes of "Selling Nature to Save It". Issue 3 (3rd May 2016) - Dempsey, Jessica; Suarez, Daniel Chiu
Abstract : Mainstream environmentalism and critical scholarship are abuzz with the promise and perils (respectively) of what we call for-profit biodiversity conservation : attempts to make conserving biodiverse ecosystems profitable to large-scale investment. But to what extent has private capital been harnessed and market forces been enrolled in a thoroughly remade conservation? In this article we examine the size, scope, and character of international for-profit biodiversity conservation. Despite exploding rhetoric around environmental markets over the last two decades, the capital flowing into market-based conservation remains small, illiquid, and geographically constrained and typically seeks little to no profit. This marginal character of for-profit conservation suggests that this project continues to underperform as a site of accumulation and as a conservation financing strategy. Such evidence is at odds with the way this sector is commonly portrayed in mainstream environmental conservation literature but also with some critical geographical scholarship. We present a more puzzling situation: Although for-profit conservation has long been promoted as a logical, easy fix to ecological degradation, it remains negligible to and largely outside of global capital flows. We argue that this project has important consequences, but we understand its effects in terms of how it reaffirms narrowed, antipolitical explanations of biodiversity loss, instills neoliberal political rationalities among conservationists, and forecloses alternative and progressive possibilities capable of resisting status quo logics of accumulation.